Effect of faba bean-based diets on the meat quality and fatty acids composition in breast muscles of broiler chickens - Kuźniacka, Joanna (Sci Rep, 2020)
The aim of the study was to evaluate the effect of feed containing faba bean on the physicochemical properties of breast and leg muscles. The study was conducted on 340 Ross 308 broiler chickens reared for 6 weeks. The control group received feed based on soybean meal. The treatment group received a feed mixture with faba bean as the source of protein. Different sources of protein in the diet were also associated with changes in the content of n-6 fatty acids (C16:0, C22:4) and the n-6/n-3 ratio in breast muscles, which was higher (P < 0.05) in treatment group. The collagen content was higher (P < 0.05) in breast muscles from control group. The study revealed that the use of faba bean as a substitute for soybean meal had no significant effect (P > 0.05) on water holding capacity, drip loss, or major chemical components of breast and leg muscles. The P/S ratio, AI and TI, and the content of cholesterol in breast muscles were comparable (P > 0.05) in both groups. The values of lightness (L*) for leg muscles were lower (P < 0.05) in treatment group. The use of faba bean instead to soybean meal in diets for broiler chickens had positive effects on meat quality traits.